Firm Characteristics, Audit Committee, and Environmental Performance: Insights from Indonesian Companies - Chariri, Anis; Januarti, Indira; Yuyetta, Etna Nur Afri (International Journal of Energy Economics and Policy, 2017)
This study aims to investigate the effect of firm size, profile of industry, independent committee audit, and audit committee meetings on environmental performance. The sample consisted of 136 companies listed on the Indonesia Stock Exchanges and receiving PROPER award issued by the Ministry of Environment, Republic of Indonesia in the year 2009-2015. The data were then analyzed using the ordinal logit regression. The findings indicated that profile of industry, independent committee audit, and audit committee meetings positively affected environmental performance. Meanwhile, firm size did not determine environmental performance. The findings imply that companies which want to create environmental performance should consider their profiles of industry and audit committee characteristics (independence and frequency of meetings). Keywords: Environmental Performance, Indonesia, Firm characteristics JEL Classifications: M48, Q51, Q56